The Legal Framework of Corporate Criminal Accountability in Indonesian Mining Crimes - Permata Mariza, Dinda (Jurnal Hukum In Concreto, 2024)
This study explores the legal framework and enforcement practices related to corporate criminal liability in Indonesia’s mining sector. While corporate accountability is formally recognized under the new Indonesian Criminal Code (KUHP 2023), Law No. 4 of 2009 on Mineral and Coal Mining (UU Minerba) lacks procedural clarity for holding corporations liable. Using a normative juridical method, the research analyzes primary legal sources and relevant secondary materials to assess how legal norms are applied in practice. The findings show a disconnect between legal recognition and enforcement. Although KUHP 2023 provides detailed provisions on corporate liability, UU Minerba remains focused on individual actors and offers no clear mechanism for attributing liability to corporate structures. As a result, prosecutions tend to target employees or subcontractors, while corporate decision-makers often evade responsibility. Enforcement is further hampered by weak institutional coordination, limited prosecutorial guidance, and political influence at the regional level. Strengthening corporate accountability requires harmonizing the KUHP and UU Minerba, developing procedural guidelines, and enhancing institutional capacity. Civil society engagement and strategic litigation are also essential to ensuring corporate compliance and promoting environmental justice.